2021
DOI: 10.1159/000519151
|View full text |Cite
|
Sign up to set email alerts
|

Digital Health for Optimal Supportive Care in Oncology: Benefits, Limits, and Future Perspectives

Abstract: <b>Background:</b> Digital health provides solutions that capture pa­tient-reported outcomes (PROs) and allows symptom monitoring and patient management. Digital therapeutics is the provision to patients of evidence-based therapeutic interventions through software applications aimed at prevention, monitoring, management, and treatment of symptoms and diseases or for treatment optimization. The digital health solutions collecting PROs address many unmet needs, including access to care and reassuranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…To achieve this, an influx of studies has suggested the use of digital devices (internet, smartphones, watches, etc) and many report promising results from this in terms of providing supportive care for cancer patients. [16,17,26] Choosing the most effective modality to collect data is important in this context. Internet-mediated interventions for patients have been reported not to be very effective as there is often a waning adherence to the use of a website over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve this, an influx of studies has suggested the use of digital devices (internet, smartphones, watches, etc) and many report promising results from this in terms of providing supportive care for cancer patients. [16,17,26] Choosing the most effective modality to collect data is important in this context. Internet-mediated interventions for patients have been reported not to be very effective as there is often a waning adherence to the use of a website over time.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this, an influx of studies has suggested the use of digital devices (internet, smartphones, watches, etc) and many report promising results from this in terms of providing supportive care for cancer patients. [16,17,26]…”
Section: Discussionmentioning
confidence: 99%